Fermented Dairy Products in the Nutrition of Infants in the Russian Federation: Past and Present - Tatiana E. Borovik; Kaleria S. Ladodo; Natalia N. Semenova; Natalia G. Zvonkova; Tatiana N. Stepanova; Tatiana V. Bushueva; Vera A. Skvortsova; Elena A. Roslavtseva; Irina M. Guseva ("Paediatrician" Publishers LLC, 2016)
Fermented dairy products have a high nutritional and biological value and functional properties beneficial to human health; they are very diverse and have a long history. Fermentation of milk is a complex technological, physical and biochemical process that occurs under the influence of two enzymes of lactic acid bacteria - -galactosidase and lactate dehydrogenase. Requirements for biological properties of starter microorganisms and fermentation technology are strictly regulated. Based on the starter cultures used, we can single out fermented dairy products of lactic acid and mixed (lactic acid and alcohol) fermentation. There are adapted, partially adapted and non-adapted cultured milk products for children, some of which are enriched with pro- and prebiotics to enhance functional properties. The article provides information about one of the first Russian non-adapted fermented milk products for infants enriched with inulin, fruit and cereals.